Poverty Rate During The 1998 and 2008 Crisis Period in 5 ASEAN Countries - Firmansyah, Ridho; Kusreni, Sri (Universitas Airlangga, 2018)
This study aims to examine and analyze the effect of GDP per capita, Inequal distribution of income, unemployment, population growth and government spending on education on poverty in five ASEAN countries. This study uses panel data regression equation using the Fixed Effect Model (FEM). The results showed that the effect of GDP per capita, Inequal distribution of income, unemployment, population growth and government spending on education affects simultaneously on poverty. While partially each independent variable have different effect on poverty in five ASEAN countries. Keywords: Poverty, Inequality Income Distribution, GDO Per Capita, Unemployment, Population Growth, Government Spending, FIxed Effect Model